Respon Pertumbuhan dan Produksi Tanaman Padi Fungsional Terhadap Penambahan Sekam Dalam Budidaya Soilless - Tirto Wahyu Widodo; Aprilia Meli Susanti; Damanhuri, Damanhuri; Muhklisin, Ilham (Politeknik Negeri Lampung., 2023)
The soaring level of public consumption and the decrease in the area of ​​cultivated land forced farmers to innovate. One of the efforts to increase healthy food production is to utilize functional rice with soilless cultivation methods. This study aimed to examine the best water and husk ratio in soilless cultivation of two functional rice varieties. This study used a completely randomized factorial design (RALF) with 2 factors and 3 replications. The first factor was water and husk soilless media with a ratio of 6:1, 8:1, 10:1, 12:1, and 14:1, while the second factor was the Watu dodol A3 and Merah A2 varieties. The results showed that the 8:1 soilless water and husk media gave the highest performance on the number of panicle grains (231,5 grains) and the number of rice panicle grains (205,67 grains). In addition, there were significant differences in plant height, productive tillers, and panicle length between Watu dodol A3 and Merah A2.